Myopia and Timira: A Cross-sectional Review of Modern and Ayurvedic Perspectives - sharma , Shikha; bavalatti , Narayana; tripathi , Ankur (International Research Journal of Ayurveda & Yoga, 2025)
Myopia is the most common refractive error and a leading cause of visual impairment worldwide, particularly affecting children and adolescents. With projections indicating that nearly half of the global population will be myopic by 2050, uncorrected refractive errors pose a significant public health concern. Modern ophthalmology primarily addresses myopia through optical correction and surgical interventions, focusing on symptom relief without altering disease progression.